Improving Islamic Education Learning Outcomes through the Course Review Horay Model: A Classroom Action Research in Elementary School - Ratnawati; Al Hamdany, M. Zuljalal; Bungawati (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
This study aims to analyze the effectiveness of the Course Review Horay (CRH) learning model in improving students’ learning outcomes in Islamic Religious Education and Character Education at SDN 16 Sampoddo. The study also seeks to examine the influence of the CRH model on students’ classroom participation, motivation, and collaborative learning engagement during the instructional process. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart cyclical model consisting of planning, acting, observing, and reflecting stages. The study was conducted in two cycles involving 23 fourth-grade students of class IVB at SDN 16 Sampoddo. Data were collected through observation, interviews, tests, and documentation. Qualitative data were analyzed through data reduction, data display, and conclusion drawing, while quantitative data were analyzed using descriptive statistics, percentage analysis, and normalized gain analysis to determine students’ learning improvement. The findings revealed that the implementation of the Course Review Horay learning model significantly improved students’ learning outcomes and classroom participation. In the pre-cycle stage, the average student score was only 36 with a classical mastery percentage of 26%. After implementing the CRH model in Cycle I, the average score increased to 73 with a mastery percentage of 52%. In Cycle II, the average score improved further to 81 with a classical mastery percentage reaching 86%. Additionally, students demonstrated higher motivation, greater self-confidence, more active classroom participation, and improved collaborative interaction during learning activities. The novelty of this study lies in the integration of joyful cooperative learning strategies within Islamic Religious Education at the elementary school level, emphasizing not only cognitive achievement but also emotional engagement and collaborative participation. This study contributes theoretically to the development of innovative Islamic education learning models and practically provides teachers with an effective instructional alternative for creating interactive, student-centered, and meaningful learning environments.